Looking up to virtue: averting gaze facilitates moral construals via posteromedial activations. Issue 11 (13th September 2018) - Yang, Xiao-Fei; Pavarini, Gabriela; Schnall, Simone; Immordino-Yang, Mary Helen
Abstract: Witnessing exemplary actions triggers admiration, a positive emotion that can pertain to concrete skills, or move the onlooker beyond physical characteristics to appreciate the abstract, moral implications. Participants reacted to narratives depicting skilled or virtuous protagonists first during a videotaped interview then during functional magnetic resonance imaging (fMRI). We analyzed participants' gaze aversion (an indicator of disengaging from the immediate environment) and cognitive construals (mentions of concrete characteristics vs abstract beliefs and values) during the interview, and relations to individuals' subsequent neural activations. When participants averted their gaze, they were more likely to mention abstract construals, and both behaviors were more likely when reacting to virtue. Gaze aversion to virtue narratives predicted greater subsequent activation for those narratives in dorsal posterior cingulate cortex (dPCC), involved in visual attention control. The inferior-posterior posteromedial cortices (ipPMC), a default mode network hub involved in abstract thought, activated only to virtue, and activity level reflected individuals' tendency to abstract construals. Critically, dPCC and ipPMC activity sequentially mediated the relationship between individuals' gaze and abstract construal tendencies. No such relationships existed for reactions to skill, despite participants reporting equivalently strong positive emotion. In appreciating virtue, dPCC may support individuals in transcending the viewable context, facilitating ipPMC activity and moral construals.